StepSafe Cane: Empowering Confident Steps for a Healthier Future - Fung Tan , Catherine Hwee; Jaafar , Nurul Aini; Goo, Hui Qi Goo; Hew, Hui Ni; Yee Law , Qian; Wong , Joe Yinn; Dhange , Mallinath Dhange (Semarak International Journal of Electronic System Engineering, 2024)
Mobility is the capability of one to get to another place. Vision is defined as the faculty and power of seeing. As technology develops and grows, several devices and tools have aided those with mobility issues or impairment and those who are visually impaired. For those who are visually impaired, the traditional aid has been the white cane for a long time which only helps them navigate their way and detect obstacles without providing physical support. While those with mobility issues use a walking stick which does not help them in detecting surrounding obstacles. For those with both mobility issues and visual impairment, this becomes a problem as it is uncommon for a gadget or aid to tackle both these issues at once. The Smart Guide Cane is specially designed for this group of people with both issues. It can also help those with any of the two issues as it has many features that will allow them to be more confident in their movement, improving the quality of life for the disabled. Many steps have been taken in developing the Smart Guide Cane. A program was coded and simulated together with the circuit to ensure the functionality of the program. Then, the physical prototype was created, using Arduino UNO, HC-SR04 (ultrasonic sensor), MPU6050 (fall detector), TTP223 (touch sensor), vibration motor and buzzer as its main components. Tests have been done using this prototype circuit to demonstrate the feasibility and functionality of the Smart Guide Cane. From the prototyping and testing, it can be seen that all the components would function as intended in the Smart Guide Cane.